Post-translational modifications are key players of the Legionella pneumophila infection strategy - Michard, Céline; Doublet, Patricia (Frontiers in Microbiology, 2015)
Post-translational modifications (PTMs) are widely used by eukaryotes to control the enzymatic activity, localization or stability of their proteins. Traditionally, it was believed that the broad biochemical diversity of the PTMs is restricted to eukaryotic cells, which exploit it in extensive networks to fine-tune various and complex cellular functions. During the last decade, the advanced detection methods of PTMs and functional studies of the host–pathogen relationships highlight that bacteria have also developed a large arsenal of PTMs, particularly to subvert host cell pathways to their benefit. Legionella pneumophila, the etiological agent of the severe pneumonia legionellosis, is the paradigm of highly adapted intravacuolar pathogens that have set up sophisticated biochemical strategies. Among them, L. pneumophila has evolved eukaryotic-like and rare/novel PTMs to hijack host cell processes. Here, we review recent progress about the diversity of PTMs catalyzed by Legionella: ubiquitination, prenylation, phosphorylation, glycosylation, methylation, AMPylation, and de-AMPylation, phosphocholination, and de-phosphocholination. We focus on the host cell pathways targeted by the bacteria catalyzed PTMs and we stress the importance of the PTMs in the Legionella infection strategy. Finally, we highlight that the discovery of these PTMs undoubtedly made significant breakthroughs on the molecular basis of Legionella pathogenesis but also lead the way in improving our knowledge of the eukaryotic PTMs and complex cellular processes that are associated to.